Evaluation of Aphrodisiac Activity of Agave americana Leaves in Male Wistar Rats (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Agave americana has been known as century plant or American aloe. This plant consists of alkaloids, flavonoids, steroidal saponins, proteins, and saponins, indicating that the plant may have aphrodisiac properties. Although traditionally, it has been used to treat inflammation, aphrodisiac nature is not evaluated. The current study was designed to evaluate the aphrodisiac activity of A. americana on male albino wistar rats. The presence of different plant constituents in the plant extract was determined by the preliminary phytochemical screening methods. For the experimental procedure, the female rats were allowed to be ovariectomized for 1 month before the behavioral activity. Hydroalcoholic extracts of A. americana at doses of 100, 200, and 400 mg /kg were administrated for 21 days. The female rats involved in mating were made receptive by hormonal treatments. The common matting behaviors, libido, potency, mounting frequency, intromission frequency and orientation activity were studied. Results revealed there was a significant raise in the mounting frequency, intromission frequency, libido activity, erection, quick flip, long flip activities. Additionally, a significant increase in the serum testosterone hormone levels in male rat was found. Current study concludes the hydroalcoholic extract of A. americana shows aphrodisiac activity at a dose of 400 mg/kg body weight.